Europe-Asia interregional relations a decade of ASEM - Gaens, Bart (International political economy of new regionalisms series, 2008)
Examines the inter-regional cooperation of the European Union with East Asia through the prism of the Asia-Europe Meeting (ASEM). This volume provides an in-depth background to ASEM and frames Europe's political and economical expectations within the post-Cold war context